The Resolution of Hidden Curriculum Implementation Problems in Islamic Boarding Schools - Saidah, Zahrotus; Syathori, Ahmad; Badriyah, Yoyoh (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
The background of this empowering society program is based on the stakeholder's concern about educators' low competence, which is marked by the lack of knowledge and skills in practising learning according to the curriculum in force. This program aims to train teachers of Islamic studies at Al Shighar Gedongan Islamic Boarding School in preparing lesson plans and learning tools based on the 7 Commitment curriculum. This hidden curriculum has been developed to emphasise strengthening character values that involve aspects of students’ knowledge, feelings, and actions. The method used in this program is Participatory Action Research (PAR), carried out in four meetings attended by 35 participants and teachers of Islamic studies subject. The results of the training activities are teachers' competence and ability to develop lesson plans and learning tools that integrate the values of the seven commitments after the pretest and post-test in 24-30 per cent.